Respiratory viral surveillance of healthcare personnel and patients at an adult long-term care facility. (25th September 2019) - O'Neil, Caroline A.; Kim, Lindsay; Prill, Mila M.; Talbot, H. Keipp; Whitaker, Brett; Sakthivel, Senthilkumar K.; Zhang, Yange; Zhang, Jing; Tong, Suxiang; Stone, Nimalie; Garg, Shikha; Gerber, Susan I.; et al.
Abstract: We conducted active surveillance of acute respiratory viral infections (ARIs) among residents and healthcare personnel (HCP) at a long-term care facility during the 2015–2016 respiratory illness season. ARIs were observed among both HCP and patients, highlighting the importance of including HCP in surveillance programs.